Metaphors we grow old by: A study of gocalıq (old age) metaphors in Azerbaijani Turkish poetry - Mostafa Shahiditabar (زبان پژوهی)
The present study attempts to probe into the reflection of aging in Azerbaijani Turkish poetry using Lakoff & Johnson’s Conceptual Metaphor Theory (CMT). The corpus of the study contains Azerbaijani Turkish poems of Shahriar (1906-1988) as well as seven other poets. A total of 50 Turkish verses on old age were recruited for this study. As an initial step, conceptual metaphors were extracted from the corpus. Then, conceptual mappings involved in each metaphor were provided. Finally, source domains in old age metaphors were obtained. The results of the paper reveal that old age is expressed through nine salient metaphors in Azerbaijani Turkish poetry. Moreover, some metaphors are shared between cultures, especially metaphors related to deterioration which are based on bodily experiences, while other metaphors are more based on the Azerbaijani culture of the poets and highly influenced by customs, traditions, religion, and economy. Also, physical deterioration rather than mental deterioration is an ideal source domain, since it is clearly delineated and people believe that they know it well.